The Use, Perception, And Knowledge Of Dietary Supplements Among Community Pharmacists - Yaser Abdalrahman Bukhari , Hassan Mohammed Alzahrani , Abdulaziz Ahmed Al Ghamdi , Ali Ahmed Alhelali , Mohammed Ali Algarni , Saadoun Nayef Saadoun Al Otaibi; Abdullah Bijad Al Osaimi , Youssef Aedh Mohammed Alqarni , Mothkir Abdullah Al-Maqati , Fahad Abbas Mohammed Hamzah , Fawaz Abdullah Abdoon Alharbi , Abdalelah Mohammed Alfhad , Humod Obaid Ganfd Alotiabi (Migration Letters, 2022)
Background: The utilization of dietary supplement (DS) is dramatically increasing across the globe, but knowledge of the community pharmacists regarding these products has not been well studied. Pharmacists are commonly tasked with recommending the appropriate DS and advising the patients of their correct and safe use. Previous research showed that they did not always use the evidence based sources of information, with personal use identified as a significant predictor influencing the decision to recommend a supplement. The study aims: To compare use, perceptions and knowledge of dietary supplements of pharmacists with different years of work experience and to explore factors that could influence their recommendation of supplements. Methods: A questionnaire based cross-sectional study was conducted on community pharmacists in Taif, KSA from January to February 2022. The questionnaire explored pharmacists’ demographic characteristics, use, perceptions and knowledge of DSs. Pharmacists (N=102) were divided in two groups based on their work experience: P0 (<10 years) and P1 (≥10 years). Results: All included pharmacists had high knowledge scores without differences between groups (P0=10,[1] IQR 9-12 vs P1=11, IQR 9-12, expressed as median and interquartile range (IQR), p=0.275). Less experienced pharmacists perceived there was less research conducted on the DSs compared to their more experienced counterparts (P0=1, IQR 1-2 vs P1=2, IQR 2-3, expressed as median and interquartile range, p<0.001). Groups differed in sources used when choosing the appropriate supplement with P0 using higher quality sources such as systematic reviews in comparison to P1 (32.1% vs. 8.7%, p=0.004). Pharmacists’ decision to recommend a DS was influenced by their personal use (odds ratio 0.216, 95%CI 0.068:0.689, p=0.01) and work experience (odds ratio 0.154, 95%CI 0.045:0.530, p=0.003). Conclusions: Pharmacists did not use the high quality sources when recommending DSs and their decision to recommend the supplement was not based on objective evaluation of evidence. Further education about the practice of evidence-based pharmacy is necessary, with special emphasis on senior pharmacists who might have missed that aspect during their formal education.